The relationship between quality of work-life and work engagement among millennial employees: psychological capital as a mediator / Mohd Azrul Azman - Azman, Mohd Azrul (2024)
This research aimed to study the relationship between quality of work-life (QWL) and work engagement, with psychological capital (PsyCap) as a mediator, among millennial employees in Malaysia. Declining work engagement has become a major concern across industries, as it negatively impacts the retention of high-talent millennial employees. The study examined how QWL influences work engagement, and the potential mediating role of PsyCap, among this demographic. A quantitative methodology was employed, with 157 millennial employees completing a questionnaire assessing work engagement, QWL, and PsyCap. Data was analyzed using SPSS and PLS-SEM. The key finding was that QWL has a significant positive relationship with work engagement. Additionally, QWL had a significant positive association with PsyCap. However, the study findings showed no significant relationship between PsyCap and work engagement among millennial employees. Furthermore, no mediating effect of PsyCap was found on the relationship between QWL and work engagement. The study opines that QWL has a strong factor directly influencing work engagement in this population. The study indicates that QWL improvements should be the primary focus for seeking to foster greater work engagement levels among millennial employees. Overall, this highlights the importance of QWL initiatives, such as supportive policies, resources, autonomy, and work-life balance, to improve work engagement among millennial employees. Organizations should also consider opportunities to enhance psychological health and well-being, which can promote work engagement. While the study had limitations in terms of geographical sample and self-reported data, it provides valuable insights into promoting work engagement among this generation. Further research with larger, more diverse samples is warranted to confirm and expand on these findings.